The impact of cell maturation and tissue microenvironments on the expression of endosomal Toll-like receptors in monocytes and macrophages. (25th August 2020) - Sato, Ryota; Reuter, Tatjana; Hiranuma, Ryosuke; Shibata, Takuma; Fukui, Ryutaro; Motoi, Yuji; Murakami, Yusuke; Tsukamoto, Hiroki; Yamazaki, Satoshi; Liu, Kaiwen; Saitoh, Shin-Ichiroh; Latz, Eicke; et al.
Abstract: Toll-like receptors (TLRs) impact myeloid cell responsiveness to environmental cues such as pathogen components and metabolites. Although TLR protein expression in monocytes and tissue macrophages is thought to be optimized for microenvironments in each tissue, a comprehensive study has not been reported. We here examined protein expression of endogenous TLRs in tissue-resident myeloid cells. Neutrophils in peripheral blood, spleen, liver and lung expressed TLR2, TLR4 and TLR5 in all tissues. Ly6C + MHC II ‒ classical monocytes mature into Ly6C ‒ MHC II + monocyte-derived dendritic cells (moDCs) or Ly6C ‒ MHC II ‒ patrolling monocytes. These subsets were found in all the tissues studied. TLR2 and TLR4 were displayed on all of these subsets, regardless of location. In contrast, expression of endosomal TLRs did vary with tissues and subsets. moDCs expressed TLR9, but much less TLR7. In contrast, TLR7, not TLR3 or TLR9, was highly expressed in classical and patrolling monocytes. Tissue macrophages such as red pulp macrophages in the spleen, Kupffer cells in the liver, microglia in the brain, alveolar macrophages in the lung and adipose tissue macrophages all expressed TLR2, TLR4 and TLR3. TLR7 was also expressed in these tissue macrophages except Kupffer cells in the liver. TLR9 expression in tissue macrophages was much lower or hard to detect. These results suggest that expression of endosomal TLRs in myeloid cells is influenced by their differentiation status and tissue-specific microenvironments. Abstract : Defining TLR protein expression in myeloid populations